What affects investment decisions among undergraduates during COVID-19 pandemic? - Chan, Hooi-Yee; Tee, Lain-Tze; Kew, Si-Roei (Penerbit Universiti Kebangsaan Malaysia, 2022)
Due to advancements in technology, increased convenience and other developments, investing has become popular among the younger generation. They can boost their income and accumulate wealth more quickly by investing. However, the investors should plan and execute trading strategies carefully before investing to avoid losing money. This study aims to investigate factors affecting investment decisions among undergraduates in the Malaysian stock market during COVID-19 pandemic. Factors examined include firm image, information, economic expectations and advocate recommendations which might influence investment decisions among investors. There are 100 undergraduates from the Universiti Kebangsaan Malaysia involved in the study. The findings indicate that firm image, economic expectations and advocate recommendations have a positive and significant relationship with investment decisions among undergraduates during COVID-19 pandemic. That is, undergraduates tend to invest in the stock market when firm image and economic expectations are optimistic while advocate recommendations are supportive. In addition, information does affect the investment decisions among undergraduates. This study is able to provide several important implications to policymakers, firms and investors.